Metabolomics Mechanistic Exploration of Traditional Chinese Medicine Dietary Intervention for Female Recurrent Urinary Tract Infections Under the Guidance of the “Medicine-Food Homology” Theory - Wang, Bingyan; Lei, Genping (Journal of Contemporary Medical Practice, 2025)
This study explores the potential mechanisms of Traditional Chinese Medicine (TCM) dietary therapy in intervening with recurrent urinary tract infections (rUTI) in women, based on the TCM theory of “food as medicine” and metabolomics technology. Starting from the core pathogenesis of “spleen-kidney damp-heat, stasis, and toxic complex,” this research analyzes the properties, flavors, and meridian tropism of spleen-strengthening and kidney-tonifying foods such as Chinese yam and Poria, as well as heat-clearing and dampness-reducing foods like Amaranth and mung beans. It combines the principles of flavor balance and meridian targeting in dietary prescriptions to elucidate their scientific connotations in regulating energy metabolism, improving oxidative stress status, controlling the gut-urinary axis microbiota, and estrogen-related metabolism, thereby repairing the urothelial barrier and enhancing mucosal immunity. The study reveals that the dietary therapy with the same origin of food and medicine acts through multi-component and multi-target synergistic effects to reshape the “host-microbiota-metabolism” balance, providing a theoretical basis for the integration of Chinese and Western medicine in the prevention and treatment of female rUTI.